Pathogenic Aspects of Inherited Platelet Disorders - Boeckelmann, Doris; Glonnegger, Hannah; Sandrock-Lang, Kirstin; Zieger, Barbara (Hämostaseologie, 2021)
Inherited platelet disorders (IPDs) constitute a large heterogeneous group of rare bleeding disorders. These are classified into: (1) quantitative defects, (2) qualitative disorders, or (3) altered platelet production rate disorders or increased platelet turnover. Classically, IPD diagnostic is based on clinical phenotype characterization, comprehensive laboratory analyses (platelet function analysis), and, in former times, candidate gene sequencing. Today, molecular genetic analysis is performed using next-generation sequencing, mostly by targeting enrichment of a gene panel or by whole-exome sequencing. Still, the biochemical and molecular genetic characterization of patients with congenital thrombocytopathias/thrombocytopenia is essential, since postoperative or posttraumatic bleeding often occurs due to undiagnosed platelet defects. Depending upon the kind of surgery or trauma, this bleeding may be life-threatening, e.g., after tonsillectomy or in brain surgery. Undiagnosed platelet defects may lead to additional surgery, hysterectomy, pulmonary bleeding, and even resuscitation. In addition, these increased bleeding symptoms can lead to wound healing problems. Only specialized laboratories can perform the special platelet function analyses (aggregometry, flow cytometry, or immunofluorescent microscopy of the platelets); therefore, many IPDs are still undetected.
Keywords: inherited platelet disorders; bleeding symptoms; primary hemostasis